Tinjauan Mengenai Penggunaan Hak Ingkar Dan Saksi A De Charge Dalam Hukum Acara Pidana (Studi Kasus Putusan Nomor : 152/PID.B/2011/PN.P BKN ) - Suliastini, Rina (Verstek, 2013)
This study aims to find out the denial right of the defendant use in the form of A De Charge witness and the implication of the denial right of the defendant use to the legal construction of judge’s authentication in investigating and sentencing narcotic case.      This study was a normative law research that was prescriptive in nature. The type of data used was secondary data. The secondary data source used included primary, secondary, and tertiary law materials. For the primary law material, the techniques of collecting data used were library study and document study. Then, the data was analyzed using systematical interpretation and syllogism deduction.      Considering the result of analysis and discussion, it could be concluded that: firstly, in each crime, the      defendant has the right to deny anything or that of not admitting the crime accused to him. This right can be called as denial right. To confirm the denial right, the defendant can propose the alleviating witness or usually called as A De Charge witness. Secondly, the existence of A De Charge witness in this narcotic case could be seen clearly. It could be seen from the judge’s deliberation in explaining that one of judge’s rationales in sentencing the defendant free was because there was the defendant’s statement denying the crime and had been supported by A De Charge witness’s testimony.       Keywords: Denial Right, A de Charge Witness, Narcotic Crime, Judge’s Legal Construction.